2014
DOI: 10.1002/jcph.354
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics, pharmacodynamics, and safety of baricitinib, an oral JAK 1/2 inhibitor, in healthy volunteers

Abstract: Baricitinib (also known as LY3009104 or INCB028050), a novel and potent small molecule inhibitor of Janus kinase family of enzymes (JAKs) with selectivity for JAK1 and JAK2, is currently in clinical development for the treatment of rheumatoid arthritis (RA) and other inflammatory disorders. Two double-blind, randomized, and placebo-controlled studies were conducted to evaluate single ascending doses of 1-20 mg and multiple ascending doses of 2-20 mg QD and 5 mg BID for 10 or 28 days in healthy volunteers. Foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
161
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(171 citation statements)
references
References 8 publications
6
161
0
4
Order By: Relevance
“…Hemoglobin remained stable during the extension period in both treatment groups. The reduction in neutrophils observed in the extension period was also observed in the first 12 weeks of the study [5] as well as in other studies of baricitinib [8,9], with similar shifts in CTCAE grade observed, and prior data indicate that transient margination of neutrophils contributed to this observation [21]. Declines in lymphocyte count were observed in some patients during the extension period.…”
Section: Discussionsupporting
confidence: 60%
“…Hemoglobin remained stable during the extension period in both treatment groups. The reduction in neutrophils observed in the extension period was also observed in the first 12 weeks of the study [5] as well as in other studies of baricitinib [8,9], with similar shifts in CTCAE grade observed, and prior data indicate that transient margination of neutrophils contributed to this observation [21]. Declines in lymphocyte count were observed in some patients during the extension period.…”
Section: Discussionsupporting
confidence: 60%
“…Importantly, several JAK inhibitors are either approved or being tested in clinical trials for the treatment of several conditions associated with DS –albeit in the typical population–, including myeloproliferative, inflammatory and autoimmune disorders, as well as leukemia (Padron et al, 2016; Spaner et al, 2016; Tefferi et al, 2011; Quintás-Cardama et al, 2010; Shi et al, 2014; Keystone et al, 2015; Jabbari et al, 2015). It should be noted, however, that the dose limiting toxicities of JAK inhibitors, like ruxolitinib, are anemia and thrombocytopenia (McKeage, 2015; Plosker, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to Fridman et al (7) and Shi et al (8), baricitinib is an novel, oral low-molecular- weight JAK inhibitor with good selectivity for JAK1 [concentration leading to 50% inhibition (IC 50 )=5.7 nM] and JAK2 (IC 50 =5.9 nM), and less selectivity for JAK3 (IC 50 >400 nM) or Tyk2 (IC 50 =53 nM), and the kidneys are considered to be the principal organ to eliminate baricitinib. Shi et al (8), Kubo et al (9) and Emery et al (10) reported that baricitinib inhibits the phosphorylation of STATs induced by various cytokines in the whole blood, and results in a transient change in neutrophil and lymphocyte counts. A previous meta-analysis suggested that the use of the JAK inhibitor tofacitinib is associated with manageable safety and increased clinical efficacy in the short-term compared with placebo (11).…”
Section: Introductionmentioning
confidence: 99%